Ultrafast myoglobin structural dynamics observed with an X-ray free-electron laser - Levantino, Matteo (Nat Commun, 2015)
Light absorption can trigger biologically relevant protein conformational changes. The light-induced structural rearrangement at the level of a photoexcited chromophore is known to occur in the femtosecond timescale and is expected to propagate through the protein as a quake-like intramolecular motion. Here we report direct experimental evidence of such ‘proteinquake’ observed in myoglobin through femtosecond X-ray solution scattering measurements performed at the Linac Coherent Light Source X-ray free-electron laser. An ultrafast increase of myoglobin radius of gyration occurs within 1 picosecond and is followed by a delayed protein expansion. As the system approaches equilibrium it undergoes damped oscillations with a ~3.6-picosecond time period. Our results unambiguously show how initially localized chemical changes can propagate at the level of the global protein conformation in the picosecond timescale.